ETNOMATEMATIKA SEBAGAI KERANGKA KERJA UNTUK MENGEMBANGKAN PENDIDIKAN MATEMATIKA YANG RESPONSIF TERHADAP BUDAYA - Nainggolan, Yusniar Arroyo; Sipangkar, Nenny Windah; Sibatuara, Jogian; Irwansyah, Mhd; Ketaren, Maya Alemina; Mailani, Elvi (Universitas Negeri Medan, 2025)
This study examines ethnomathematics as a discourse for the development of culturally responsive mathematics education within a multicultural context. The purpose of this study is to explore the relationship between ethnomathematics, multicultural education, and local wisdom in enhancing meaningful mathematics learning. This research employs a qualitative approach through a literature review, analyzing relevant books, journal articles, and previous studies related to ethnomathematics and multicultural education. The findings indicate that ethnomathematics plays a significant role in connecting mathematical concepts with students’ cultural backgrounds and everyday experiences. Integrating local wisdom into mathematics learning not only increases student engagement and conceptual understanding, but also strengthens cultural identity and appreciation of diversity. Furthermore, ethnomathematics supports the construction of mathematical knowledge that is contextual, relevant, and socially meaningful. In the context of multicultural education, ethnomathematics contributes to equal learning opportunities by valuing diverse cultural perspectives in mathematics instruction. This study concludes that the integration of ethnomathematics into mathematics curricula is a strategic approach to developing cultural mathematics education that aligns with the principles of multiculturalism and holistic learning.